ANALISIS KETEBALAN PELAT DAN PENENTUAN SISA UMUR PAKAI PADA TANGKI 2 DI PLTMG AMBON PEAKER - Mahubessy, Nurul Fadhila; Effendy, Edison; Lilipaly, Eka R. M. A. P. (Journal Mechanical Engineering, 2024)
ABSTRACTThe Ambon Peaker Gas Power Plant (PLTMG Ambon Peaker) is an electrical infrastructure facility powered by gas turbines, located in Waai Village, Central Maluku Regency, Maluku Province. The fuel oil storage tank used by the Ambon Peaker since 2019 is situated directly near the coastline, making it very vulnerable to damage, particularly from corrosion on its metal plate walls. Therefore, maintenance is necessary to prevent any unwanted workplace accidents. This tank stores fuel oil. The author conducted calculations for minimum thickness and corrosion rate to determine the remaining lifespan of the tank. The results indicate that the critical point is located at course 1, with a remaining lifespan of 121 years. This can be influenced by various factors, such as environmental conditions and fluid characteristics. Tank maintenance also needs to be considered to ensure the tank's reliability, allowing it to operate longer and preventing the need for corrective maintenance. Keywords: storage tank, corrosion rate, wall thickness, remaining life.